2020
DOI: 10.21203/rs.3.rs-42653/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided fine-needle aspiration of pelvic lesions via the upper and lower gastrointestinal tract approaches

Abstract: Background: Combining upper and lower gastrointestinal tract (GI) approaches allows expansion of endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) indications for pelvic lesions. The upper GI approach has been used for pelvic lesions around the level of the aortoiliac bifurcation in our institution. The aim of this study is to evaluate the feasibility and safety of EUS-FNA for pelvic lesions via the upper and lower GI approaches. Methods: All consecutive patients who underwent EUS-FNA for the pelvi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…To date, many studies involving EUS-FNA have focused on applications in diagnosing space-occupying lesions in the pancreas, liver, and mediastinum. However, few studies have reported on the use and diagnostic accuracy of EUS-FNA in pelvic space-occupying lesions (11)(12)(13)(14). In the present study we retrospectively analyzed the medical records of 35 patients who underwent EUS-FNA for pelvic space-occupying lesions at our hospital over a 7-year period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, many studies involving EUS-FNA have focused on applications in diagnosing space-occupying lesions in the pancreas, liver, and mediastinum. However, few studies have reported on the use and diagnostic accuracy of EUS-FNA in pelvic space-occupying lesions (11)(12)(13)(14). In the present study we retrospectively analyzed the medical records of 35 patients who underwent EUS-FNA for pelvic space-occupying lesions at our hospital over a 7-year period.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of 21 patients with pelvic space-occupying lesions concluded that the diagnostic sensitivity of EUS-FNA via the lower digestive tract for malignant pelvic space-occupying lesions was 94.4%, the specificity was 100.0%, the positive predictive value was 100%, the negative predictive value was 66.7%, and the accuracy was 95.0% (12). A meta-analysis of 10 studies involving 246 patients with pelvic space-occupying lesions (13) showed that the diagnostic sensitivity of EUS-FNA for differentiating between benign and malignant lesions was 89.0%, the specificity was 93.0%, and the overall incidence of complications was 1.7% (there was 1 case of postpuncture bleeding and 2 cases of secondary abscesses after puncture of the cystic lesions) (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, CLA probes have an oblique endoscopic view that makes deep insertion into the colon technically challenging and potentially risky due to complex anatomical factors and colonic angulations that discourage its use beyond the rectosigmoid colon. 5,6 However, the diagnostic and therapeutic uses of CLA-EUS in the…”
Section: Discussionmentioning
confidence: 99%
“…Infection and pneumoperitoneum have been reported after EUS-FNA of pelvic and rectosigmoid lesions. 6,9 Another concern about C-US FNA is the risk of neoplastic cell seeding. To the best of our knowledge, there are no current data on C-US FNA, and therefore, it should be considered only if performing FNA would be crucial to management decisions.…”
Section: E83mentioning
confidence: 99%